Strategi Guru Dalam Meningkatkan Minat Belajar Peserta Didik Pada Mata Pelajaran PAI di MTsN 15 Tanah Datar - Febby, Febby; Trisno , Bambang; Rodhiawati, Rodhiawati (Indonesian Research Journal on Education, 2023)
In the teaching and learning process, of course, we must first know what strategies we use to increase students' interest in learning. to increase students' interest in learning so that in class learning students can better understand the lessons the teacher has explained and be more enthusiastic about carrying out the learning process. learners can better understand the lessons the teacher has explained and be moreenthusiastic about the learning process. learning process. In the context of the interaction of the learning process, students experience a tendency to lack motivation in learning. tendency to be less motivated in learning. This research reveals efforts to increase students' interest in learning, and students' learning activities, the teacher's ability to provide learning motivation and also students' learning responses through classroom lessons. This study aims to increase students' interest in learning, determine students' learning activities, the teacher's ability to provide learning interest, and also determine students' learningresponses through classroom learning. Various strategies can be applied by teachers through learning in the classroom so that students are interested in learning. However, teachers are required to have creativity and innovation in creating a conducive and effective learning atmosphere.